Strategi Komunikasi Pengemudi GoRide di BALI dalam Meningkatkan Pelayanan Pengguna - Lidwina Putu Lia Elvina; Yulita Daru Priliantari (Jurnal Ilmu Komunikasi Widyanita, 2026)
This study aims to analyze the communication strategies applied by GoRide drivers in providing services to users in Bali, particularly within the tourism context, which is characterized by cultural diversity and varying communication needs. Using a qualitative approach through interviews and observation, the study finds that the communication strategies of GoRide drivers are strongly influenced by the principles of Communication Accomodation Theory (CAT). The result indicate that drivers consistently apply convergence strategies by adjusting their speaking style, intonation, and word choice, as well as by using polite Indonesia, simple English, and refined Balinese language. Drivers also employ nonverbal expressions such as smiling and positive body language to create comfort. Divergence strategies are applied to maintain professional boundaries, including reducing conversation when passengers appear tired, wear earphone, or during heavy traffic conditions. Balinese cultural values such as politenss, friendliness, and respect further strengthen the drivers communication patterns. In addition, drivers utilize technology such as Google Translate to overcome language barriers. Overall, these adaptive communication strategies are shown to enhance passenger comfort, satisfacation, and the positive public image of GoRide services in Bali.